EFFECT OF CONCENTRATION AND APPLICATION DURATION OF EMS ON IN VITRO ROOT FORMATION OF CAMAROSA STRAWBERRY (FRAGARIA X ANANASSA) - SANDHYA BHAT; SUNEEL SHARMA; VIKAS KUMAR SHARMA; P. S. PRATAP; SUBHASH KAJLA (The Bioscan, 2015)
In the present investigation, experiment was conducted to create variability through induced mutations in different explants of strawberry cv. Camarosa. Different EMS concentrations (0.1 %, 0.2%, 0.3% and 0.4%) along with control for various treatment durations (1.5 hr, 2.5 hr and 3.5 hr) used for the induction of variation. The concentration 0.4% was found lethal to the plants. Among different concentrations of EMS tried, 0.1% was found best followed by 0.2% and 0.3%. Among different durations treated, 1.5 hr was found best followed by 2.5 hr and 3.5 hr. While among various explants used, the runner tips explants was found best followed by shoot tips, leaf disc (abaxial) and leaf disc (adaxial). The EMS dose of 0.1% applied for 1.5 hr on runner tip explants was found best combination among all treatments in terms of in vitro root growth parameters recorded viz., initiate early roots (45.3 days), maximum number of roots (32.5) and maximum length of roots (55.5 mm). As the increased EMS concentrations along with treatment duration there was a gradual decrease in growth and development of plants. In future, these experimental results will prove very useful for induction of variability in this fruit crops.